2019
DOI: 10.1093/jscr/rjz121
|View full text |Cite
|
Sign up to set email alerts
|

Repeat presentation of large rectal foreign body requiring surgical intervention

Abstract: Irretrievable rectal foreign bodies can cause significant distress and generally require emergency medical attention. While smaller objects can often be removed trans-anally, larger objects typically require more invasive intervention. Here, we report the case of a 57-year-old man who had previously presented to the emergency department with a baseball lodged in the rectosigmoid that required a laparotomy. One year later, he represented with a significantly larger object also affixed in the rectosigmoid. Explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…On the other hand, the majority of the studies consulted are in agreement that this type of problem has been reported from as early as 15 years, and that the upper age has virtually no limit, presenting a peak between 30 and 59 years, and averaging at an age of 40 years (10). In relation to sex, it is defi nitely much more frequent in men than in women, 87% vs. 13%, which also corresponds with that in the world literature (1,7,11). This work also includes data on education level and marital status that were not reported in other works.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…On the other hand, the majority of the studies consulted are in agreement that this type of problem has been reported from as early as 15 years, and that the upper age has virtually no limit, presenting a peak between 30 and 59 years, and averaging at an age of 40 years (10). In relation to sex, it is defi nitely much more frequent in men than in women, 87% vs. 13%, which also corresponds with that in the world literature (1,7,11). This work also includes data on education level and marital status that were not reported in other works.…”
Section: Discussionsupporting
confidence: 83%
“…However, Dahlberg et al (8), in their study of the insertion of sex toys, report that manual removal was not successful in 73% of cases. In this situation the authors reported the need for laparotomy in 8 of 85 cases (9.5%), colonoscopy in 3 cases (3.5%), vs. 5% and 2.5%, respectively reported in this work., it was not possible to establish the cause of these statistical differences in the reports; however while smaller objects can often be removed transanally, it is possible to consider that larger objects typically require a more invasive intervention (11). What is clear in the literature is that surgery will be required if the object reaches the sigmoid (10,18).…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of rectal foreign body (RFB) although relatively uncommon [5] , [6] , [7] is no longer a medical oddity as it's encountered more frequently recently [7] , [8] , [9] , [10] with increasing incidence especially in urban areas [11] , [12] . Yet the diagnosis and management can be challenging [12] due to multiple reasons, including reasons related to the patient’'s feeling of embarrassment which makes him reluctant to provide details of the incident and to seek medical help only after trying several times to self-extract the object, which could complicate the situation even more and delay timely management [8] , [12] , [13] , it's reported that only 33.3% of the cases of RFB present a history of anal introduction [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the reasons for insertion, RFB is either inserted voluntarily; most commonly for sexual gratification 75% [5] , [17] whether autoeroticism or as a consensual sexual act [19] , or for treating anorectal conditions, for example to relieve fecal impaction, or for prostate massage, especially in the elderly [20] , in drug traffickers as body packs [17] , in prisoners hiding objects especially to harm others [21] , and in the psychiatric patients including those with factitious disorders such as Munchausen's syndrome as the case reported by Khan et al [19] . In others, RFBs are involuntarily inserted as in sexual assaults and rape, accounting for 12.5% of cases [21] , in which cases legal authorities should be notified [18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation